2015
DOI: 10.1155/2015/362562
|View full text |Cite
|
Sign up to set email alerts
|

Human Urine as a Noninvasive Source of Kidney Cells

Abstract: Urine represents an unlimited source of patient-specific kidney cells that can be harvested noninvasively. Urine derived podocytes and proximal tubule cells have been used to study disease mechanisms and to screen for novel drug therapies in a variety of human kidney disorders. The urinary kidney stem/progenitor cells and extracellular vesicles, instead, might be promising for therapeutic treatments of kidney injury. The greatest advantages of urine as a source of viable cells are the easy collection and less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 82 publications
1
50
0
Order By: Relevance
“…As isolation of USCs does not require tissue dissociation procedures, cell viability is better protected, since no digestive enzymes are involved [17,20]. Our recent data and results from other investigators demonstrated that USCs have optimal regenerative potential for regeneration of bladder [24], kidney [25][26][27], corpora cavernosa [10,28], bone [29][30][31][32], lungs [33], skin [34], nerve [35], and other types of tissue [30,32,34,[36][37][38][39][40][41]. These cells are safe to use in vivo without any risk of oncogenicity [7,28,42].…”
Section: Discussionmentioning
confidence: 92%
“…As isolation of USCs does not require tissue dissociation procedures, cell viability is better protected, since no digestive enzymes are involved [17,20]. Our recent data and results from other investigators demonstrated that USCs have optimal regenerative potential for regeneration of bladder [24], kidney [25][26][27], corpora cavernosa [10,28], bone [29][30][31][32], lungs [33], skin [34], nerve [35], and other types of tissue [30,32,34,[36][37][38][39][40][41]. These cells are safe to use in vivo without any risk of oncogenicity [7,28,42].…”
Section: Discussionmentioning
confidence: 92%
“…To establish a potentially direct assessment of APOL1 mRNA expression in kidney, we measured APOL1 mRNA in urinary shed cells collected from our APOL1-transgenic mice. Urinary shed cells are a mixture of various cell types composed of podocytes, proximal tubule epithelial cells, and kidney stem/progenitor cells (30). We explored whether expression of APOL1 mRNA in urinary shed cells could be used as a noninvasive method to measure APOL1 mRNA levels in kidney.…”
Section: Resultsmentioning
confidence: 99%
“…We found no evidence for necrosis, apoptosis, or autophagic cell death after analyzing multiple sections from multiple mice. Alternatively, rodent and human studies have shown podocytes can detach from the glomerulus without dying (reviewed in Oliveira Arcolino et al 33 ). Since WT-1 immunostaining was used to quantify podocytes, missing podocytes may be present but dedifferentiated and no longer expressing WT-1.…”
Section: Discussionmentioning
confidence: 99%